Vírus da Hepatite C: prevalência dos genótipos, fatores de risco, alterações bioquímicas e histopatológicas de pacientes atendidos no Núcleo de Medicina Tropical - FECURY, Amanda Alves (Universidade Federal do Pará, 2013)
The hepatitis caused by HCV is a silent disease that tends to develop into the chronic form. The viral persistence depends on genetic factors of the individual and the virus (genotypes), lifestyle and exposure to risk factors increase the chances of the carrier to develop hepatocellular carcinoma. This study objective to check the liver function of patients with hepatitis C and evaluate the risk factors for acquiring the virus and determine the most prevalent HCV genotypes and the genotypes correlate with histopathologic findings of liver biopsies.. The sample consisted of 152 adult patients with reagent serology (ELISA) for anti-HCV, who agreed to participate, collected blood samples for analysis and answered an epidemiological questionnaire. Epidemiological analysis showed most male, age 45 years and a predominance of married or stable individuals. Regarding risk factors for acquiring the infection, there was a multiplicity of partners, not condom use, hospitalizations, and manicure kits share. In the detection of viral RNA, 107 (70,4%) were positive, with 97 (90,6%) genotype 1 and 10 (9,4%) genotype 3. There was no variation in the biochemical assays, the genotypes and histophatological changes. Of the 65 patients who underwent liver biopsy and histopathological examination, all patients had chronic hepatitis. Analyzing the histopatological changes and viral genotypes found association of these variables, with the genotype 1 related histological changes more intense. The results are in agreement with other previously reported.